Fuzzy logic based MPPT technique for energy conversion - Mohit, Kumar; Mohanty, S.K. (International Journal of Advances in Applied Sciences, 2021)
World is facing acute energy crisis as a result of which there is a need for renewable energy sources. Increase in demands and environmental issues lead to rise in renewable energy. Solar energy is being increasing and is being adopted by many countries but the output power is not constant because of two factors radiation and temperature. And also photo voltaic V-I characteristics are non linear in nature. So MPPT algorithm is applied to increase the overall efficiency. There are many MPPT algorithms and everyone has their own advantages and disadvantages. Perturb and observe are most commonly used MPPT technique because of its simplicity. But it has some drawbacks also. This paper uses Fuzzy logic algorithm as well as Perturb and Observe tracking algorithm for optimizing maximum power point. After simulation and analysis in Matlab the results indicate that Fuzzy logic algorithm is better than perturb and observe because of its high convergence rate, more stability, fast time response and less overshoot. A complete PV system contrastingly comprises boost converter, MPPT algorithm, PV array, and a load mainly resistive type.